(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Over the last half a century and particularly, in the recent decades, teaching learning has been undergoing drastic changes. There has been a shift towards student centered classrooms with teacher’s role more as facilitator of learning rather than an autocratic master. Unlike in the past when the teacher was entrusted with transferring the contents of curriculum to a passive audience of students, today new experiments are being tried out in the classroom that includes project based learning, development of thinking skills, and discovery learning approaches. As part of Sarva Shiksha Abhiyan (SSA) the textbooks have also been modified (in my opinion, to make them worse than before in many respects).Many teachers are not properly trained in implementing the concepts behind the new curriculum and many are not equipped to properly implement the curriculum.